Demographic history and biologically relevant genetic variation of Native Mexicans inferred from whole-genome sequencing - Sandra Romero-Hidalgo (Nature Portfolio, 2017)
People of Mexico have diverse historical and genetic background. Here, Romero-Hidalgo and colleagues sequence whole genomes of Native Americans of Mexico, and show demographic history and genetic variation shared among subgroups of Native Americans.